Δ-FeOOH as Support for Immobilization Peroxidase: Optimization via a Chemometric Approach - Tavares, Tássia Silva; da Rocha, Eduardo Pereira; Esteves Nogueira, Francisco Guilherme; Torres, Juliana Arriel; Silva, Maria Cristina; Kuca, Kamil; Ramalho, Teodorico C (Molecules (Basel, Switzerland), 2020)
Owing to their high surface area, stability, and functional groups on the surface, iron oxide hydroxide nanoparticles have attracted attention as enzymatic support. In this work, a chemometric approach was performed, aiming at the optimization of the horseradish peroxidase (HRP) immobilization process on Δ-FeOOH nanoparticles (NPs). The enzyme/NPs ratio (X1), pH (X2), temperature (X3), and time (X4) were the independent variables analyzed, and immobilized enzyme activity was the response variable (Y). The effects of the factors were studied using a factorial design at two levels (-1 and 1). The biocatalyst obtained was evaluated for the ferulic acid (FA) removal, a pollutant model. The materials were characterized by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The SEM images indicated changes in material morphology. The independent variables X1 (-0.57), X2 (0.71), and X4 (0.42) presented the significance effects estimate. The variable combinations resulted in two significance effects estimates, X1*X2 (-0.57) and X2*X4 (0.39). The immobilized HRP by optimized conditions (X1 = 1/63 (enzyme/NPs ratio, X2 = pH 8, X4 = 60 °C, and 30 min) showed high efficiency for FA oxidation (82%).
Keywords: enzymy imobilizované; Enzymes, Immobilized; iron oxide hydroxide; spektroskopie infračervená s Fourierovou transformací; Nanoparticles; X-Ray Diffraction; Oxidation-Reduction; křenová peroxidasa; bioremediation; Ferric Compounds; Spectroscopy, Fourier Transform Infrared; kyseliny kumarové; železité sloučeniny; horseradish peroxidase; biokatalýza; Biocatalysis; Horseradish Peroxidase; nanočástice; immobilization; oxidace-redukce; Coumaric Acids; difrakce rentgenového záření